THE EFFECT OF ADDITION OF QUARTZ SAND AS A MATERIAL FOR SOIL STABILIZATION REVIEWED FROM CBR VALUE (CALIFORNIA BEARING RATIO) - Masta'in, Masta'in; Hariyanto, Hariyanto; Ferdian Eka Ramadhan, Muhammad (Universitas PGRI Semarang, 2025)
This study aims to analyze the effect of adding quartz sand as a soil stabilizing agent on CBR (California Bearing Ratio) values. Methods of soil stabilization using quartz sand were investigated to understand the potential for increasing soil carrying capacity. CBR testing was carried out to compare the characteristics of the stabilized soil with that of the original soil. Various percentages of quartz sand addition (0%, 5%, 10%, and 15%) were tested in this study. The CBR test results showed that the addition of quartz sand increased the CBR soil stabilization value compared to the original soil. The results showed that there was a significant increase in soil stabilization and carrying capacity with the addition of quartz sand. However, there is an optimal limit on the proportion of adding quartz sand that gives the highest CBR value, where after reaching a certain point, the increase in the CBR value becomes slower. This research provides insight into the potential use of quartz sand as a soil stabilizing agent in improving soil carrying capacity, which can be applied in infrastructure construction and geotechnical engineering..Keywords: CBR(California Bearing Ratio), Standard Proctor, Quartz Sand